2022
DOI: 10.1055/s-0042-1758638
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Analysis Evaluating the Safety of Using Acellular Dermal Matrix with Tissue Expander-Based Breast Reconstruction

Abstract: Background In March 2021, the United States Food and Drug Administration (FDA) safety communication cautioned against the use of acellular dermal matrix (ADM) products in breast reconstruction and reiterated that the FDA does not approve ADM use in breast surgery. This study aims to assess the safety of ADM use in breast reconstruction. Methods Women who underwent ADM and non-ADM assisted tissue expander (TE)-based breast reconstruction were identified using the National Surgical Quality Improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Additionally, they find application in addressing full‐thickness skin defects arising from various sources, including traumatic injuries, post‐melanoma surgical resections and breast reconstruction procedures. 28 , 29 , 30 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, they find application in addressing full‐thickness skin defects arising from various sources, including traumatic injuries, post‐melanoma surgical resections and breast reconstruction procedures. 28 , 29 , 30 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they find application in addressing fullthickness skin defects arising from various sources, including traumatic injuries, post-melanoma surgical resections and breast reconstruction procedures. [28][29][30] A study by Bloemen et al showed improved scar parameters in 34 reconstructive wounds treated with Matriderm ® compared with split-thickness skin graft alone in a 12-year follow-up of 26 patients. 3 Moreover, the effectiveness of dermal substitution in acute burn wounds was shown in long-term scar elasticity when a dermal substitute was used in combination with topical negative pressure (TNP) therapy versus substitute alone (respectively 21 and 23 patients).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation